Human molar dentinal tubules and its odontoblast process. A combined investigation using variable pressure scanning electron microscope and image analysis - Ghazali, Farid Che; Noor, Syed Hatim; Asan, Jamaruddin Mat (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Electron microscopy studies of the dentinal tubules are mainly investigated using the high vacuum conventional scanning electron microscope (SEM). We aimed to investigate its morphology using the variable pressure SEM Three almost caries free intact adult human molar tooth were prepared as unembedded demineralised whole dentine preparations that were initially chemically fixed with 1 Oo/o formalin for 24 hours. They were demineralised in 1 0°/o EDTA solution for 4 weeks following, which they were than section into two equal halves. The uncoated partially demineralised dentine half tissue was inspected systematically under a LEO VPSEM using the peltier cooling sub stage at 15 Pascal pressure with an accelerating voltage of 15 kV. An occlusal and longitudinal observation was made from its occlusal surface to the pulpal border. Both low and high magnifications images were prepared from each specimen observed.